Home Grown : Marijuana and the Origins of Mexico's War on Drugs - Campos, Isaac (Book collections on Project MUSE., 2012)
Historian Isaac Campos combines wide-ranging archival research with the latest scholarship on the social and cultural dimensions of drug-related behavior in this telling of marijuana's remarkable history in Mexico. Introduced in the sixteenth century by the Spanish, cannabis came to Mexico as an industrial fiber and symbol of European empire. But, Campos demonstrates, as it gradually spread to indigenous pharmacopoeias, then prisons and soldiers' barracks, it took on both a Mexican name--marijuana--and identity as a quintessentially "Mexican" drug. A century ago, Mexicans believed that marijua.